TRAINING ON IMPROVING THE QUALITY OF NURSING CARE THROUGH THE APPLICATION OF 3S (SDKI, SLKI AND SILKI) - Eldessa Vava Rilla, Eldessa Vava Rilla; Tantri Puspita, Tantri Puspita; Sulastini, Sulastini; Aceng Ali Awaludin, Aceng Ali Awaludin; Herlin Rusyani, Herlin Rusyani; Taufik Huda, Taufik Huda (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Nursing care service standards cannot be separated from the nursing process, which is the main task of nurses in providing nursing care. This process starts from assessment, establishing a nursing diagnosis, preparing a nursing care plan, implementing and evaluating the success of the care provided. The services provided by the nursing profession are providing nursing services. The SDKI is a diagnostic standard that can be used in nursing clinical decision making based on ease of use, clarity of diagnostic reasoning and completeness of the types of diagnoses available as well as language standards. One of the main factors influencing the implementation of nursing documentation based on SDKI, SIKI, and SLKI is knowledge nurse in Nurhayati Garut Hospital